2022
DOI: 10.36348/jaspe.2022.v05i08.001
|View full text |Cite
|
Sign up to set email alerts
|

Load Dynamics, Recovery and Adaptation for Better Sporting Events

Abstract: International result-oriented performance in sports requires systematic scientific training. A proper pedagogical approach is required for systematic loading of the athletes in order to record-breaking performance. The performance of an athlete largely depends upon a progressive training load for a relatively long period of time. The degree of mechanical tension, subcellular damage, and metabolic stress can all play a role in exercise-induced muscle adaptations. The process of adaptation largely depended upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Appropriate training frequency may help recover physical performance and realize super-compensation, which eventually contributes to accumulating RT training effects [41][42][43]. In traditional RT, a frequency of 1 to 5 times per week can increase muscle strength [19,33].…”
Section: Frequencymentioning
confidence: 99%
“…Appropriate training frequency may help recover physical performance and realize super-compensation, which eventually contributes to accumulating RT training effects [41][42][43]. In traditional RT, a frequency of 1 to 5 times per week can increase muscle strength [19,33].…”
Section: Frequencymentioning
confidence: 99%
“…The recovery process is crucial for athletes to maintain peak performance and prevent injuries. Research has shown that factors such as sleep, nutrition, stress, and training load dynamics play a significant role in an athlete's recovery (1,2). Additionally, the use of recovery strategies, such as massage therapy, active recovery, and relaxation interventions, has been found to positively impact athletes' recovery (3).…”
Section: Introductionmentioning
confidence: 99%